1992
DOI: 10.1002/art.1780350206
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Assessment of Disease Activity in Rheumatology (Radar) Questionnaire

Abstract: Objective. This study documents the measurement properties of a brief, self-administered questionnaire of disease signs and symptoms in patients with rheumatoid arthritis. Measurement of disease signs and symptoms is a key aspect of outcome evaluation in rheumatology-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Physicians recorded affected joint scores and numbers and overall disease activity. Self-assessment by patients was performed by using the Rapid Assessment of Disease Activity in Rheumatology (24). Both physician-and patient-generated data showed a marked improvement from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians recorded affected joint scores and numbers and overall disease activity. Self-assessment by patients was performed by using the Rapid Assessment of Disease Activity in Rheumatology (24). Both physician-and patient-generated data showed a marked improvement from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…23 Separate ratings made for each of 20 joints or joint groups (from 0 ϭ no joint pain or tenderness to 3 ϭ severe joint pain or tenderness) were summed for analysis. The within-person internal consistency of this scale was .88.…”
Section: Daily Joint Painmentioning
confidence: 99%
“…Functions related to movements of lower extremities have been suggested to play an important role in RA patients' disability [18,19]. However, the ROAD questionnaire development suggested that upper extremity functions explain most of the variance.…”
Section: Realtive Importance Of Functions 8 Discussionmentioning
confidence: 99%